Accounting for dynamics in flexible process design: A switchability index. (February 2021) - Di Pretoro, Alessandro; Montastruc, Ludovic; Joulia, Xavier; Manenti, Flavio
Highlights: Uncertain operating conditions can compromise the control loop performances even in case optimized tuning parameters. When accounting for dynamic flexibility, the optimality of the designed control structures can considerably differ with respect to the results obtained with the conventional procedure. The defined switchability index and the related graphical representations have proved to be quick and effective tools to compare different design configurations and to assess the impact of dynamics from a flexibility point of view. Abstract: Flexible operations design is one of the key challenges of process engineering over the last years. However, even when uncertainty during the design phase is taken into account, the vast majority of research works refer to steady state conditions only, neglecting the system behaviour during the transition from the nominal state to the perturbed one. The final design validation indeed can be obtained only accounting for process dynamics, i.e. for the process control configuration. This research work then carries out the dynamic flexibility assessment both for simple and more complex systems, such as a CSTR and a distillation column case studies. The deep insight into the dynamics of operating conditions that change in time allows the definition of a new switchability index able to describe the relationship between dynamic and steady state performances from a flexibility point of view. This additional indicator provided to the decision maker resulted to be a quick and effective tool to carry out a more conscious design choice. Beside allowing a more reliable equipment sizing, it enables the comparison between different control strategies as well as different tuning methodologies and the identification of the optimal ones related to different flexibility ranges. Furthermore, this innovative indicator results suitable to be exploited in a future perspective for the optimization of startup and shutdown procedures.